Targeted genome editing in polyploids: lessons from Brassica - Ahmad, Niaz; Fatima, Samia; Mehmood, Muhammad Aamer; Zaman, Qamar U.; Atif, Rana Muhammad; Zhou, Weijun; Rahman, Mehboob-ur; Gill, Rafaqat Ali (Frontiers in Plant Science, 2023)
CRISPR-mediated genome editing has emerged as a powerful tool for creating targeted mutations in the genome for various applications, including studying gene functions, engineering resilience against biotic and abiotic stresses, and increasing yield and quality. However, its utilization is limited to model crops for which well-annotated genome sequences are available. Many crops of dietary and economic importance, such as wheat, cotton, rapeseed-mustard, and potato, are polyploids with complex genomes. Therefore, progress in these crops has been hampered due to genome complexity. Excellent work has been conducted on some species of Brassica for its improvement through genome editing. Although excellent work has been conducted on some species of Brassica for genome improvement through editing, work on polyploid crops, including U’s triangle species, holds numerous implications for improving other polyploid crops. In this review, we summarize key examples from genome editing work done on Brassica and discuss important considerations for deploying CRISPR-mediated genome editing more efficiently in other polyploid crops for improvement.